2019
DOI: 10.1016/s0140-6736(18)32591-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects, equity, and cost of school-based and community-wide treatment strategies for soil-transmitted helminths in Kenya: a cluster-randomised controlled trial

Abstract: Summary Background School-based deworming programmes can reduce morbidity attributable to soil-transmitted helminths in children but do not interrupt transmission in the wider community. We assessed the effects of alternative mass treatment strategies on community soil-transmitted helminth infection. Methods In this cluster-randomised controlled trial, 120 community units (clusters) serving 150 000 households in Kenya were randomly assigned (1:1:1) to recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 26 publications
4
106
1
Order By: Relevance
“…Multiple studies have focused on the effectiveness and acceptability of MDA for these diseases [5][6][7][8]; however, there is limited evidence supporting the use of community-wide MDA for STH. The TUMIKIA Project, conducted in Kenya, was the first cluster randomized control trial assessing the effectiveness, equity, and cost of school-based versus community-wide treatment strategies on the prevalence and intensity of STH infection [9,10]. The impact results concluded that community-wide MDA was more effective in reducing hookworm prevalence and intensity across all age groups than school-based delivery, providing much needed evidence on the feasibility and effectiveness of community-wide MDA for STH control [9].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have focused on the effectiveness and acceptability of MDA for these diseases [5][6][7][8]; however, there is limited evidence supporting the use of community-wide MDA for STH. The TUMIKIA Project, conducted in Kenya, was the first cluster randomized control trial assessing the effectiveness, equity, and cost of school-based versus community-wide treatment strategies on the prevalence and intensity of STH infection [9,10]. The impact results concluded that community-wide MDA was more effective in reducing hookworm prevalence and intensity across all age groups than school-based delivery, providing much needed evidence on the feasibility and effectiveness of community-wide MDA for STH control [9].…”
Section: Introductionmentioning
confidence: 99%
“…(B.11) 11 There is a subtlety here in the choice of initial condition: due to the discontinuity at the boundary, an additional component of βδL(t pul ) t pul e −µ 2 (t−t pul ) dt β µ 2 δL(t pul ) must be added to the initial worm burden from the infectious reservoir pulse, such that M(t 0 ) = M(t pul ) + β µ 2 δL(t pul ).…”
Section: Discussionmentioning
confidence: 99%
“…Eqs. (11) and (13) thus immediately indicate that a mechnism for fluctuation to or away from the equilibria in, e.g., Fig. 1, is possible and that a deeper study of the dynamics of the system is necessary in order to fully understand the ramifications.…”
Section: Perturbing the System With Migrationmentioning
confidence: 95%
See 1 more Smart Citation
“…Study design, baseline findings, and impact have been described previously (17, 18) (Halliday KE, Oswald WE, Mcharo C, Beaumont E, Gichuki PM, Kepha S, et al Community-level epidemiology of soil-transmitted helminths in the context of school-based deworming: Baseline results of a cluster randomised trial on the coast of Kenya. In Press).…”
Section: Methodsmentioning
confidence: 99%